A 'de Soto Effect' in Industry? Evidence from the Russian Federation - William Pyle; Koen Schoors (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
Russia's tremendous inter-regional variation in the pace of industrial land rights reform has meant that geography has helped determine the current tenure status of firms' production plots as much as any individual firm characteristics. By exploiting both this difference in the pace with which land reform has been carried out across Russia's federal subjects and a unique micro-level dataset, we present evidence strongly consistent with the proposition that more secure rights to land facilitate access to external financing. This finding is confirmed by other evidence from the survey that points to private land serving as an important source of collateral for Russian lenders and borrowers.
URN:NBN:fi:bof-201408071963
Keywords: O16; P25; P31; R14; R52; 330; industrial land; property rights; Russia; collateral